Efficacy of a Single 5,000 IU Dose of HCG in Enhancing Pregnancy Outcomes During Early Gestational Period (Journal of Rangpur Medical College, 2025)
Background: Human chorionic gonadotropin (HCG) has an important role in maintaining early pregnancy and has been studied to improve pregnancy outcomes. Objective: This study aimed to assess the effectiveness of a single 5,000 IU dose of HCG in improving early pregnancy outcomes for women at risk of complications. Methods: This prospective study was conducted at the Salauddin Specialized Hospital, Dhaka, Bangladesh, from January 2023 to January 2024 on 120 pregnant women in the early stages of pregnancy at 6 weeks without cardiac pulsation and positive β-hCG levels. They were randomly divided into two groups: the HCG group (n=60), which received 5,000 IU of intramuscular HCG, and the control group (n=60), who received standard care. The main outcomes included ongoing pregnancy rates, miscarriage rates, positive HCG levels, fetal heartbeat detection at 8 weeks, and hormone levels measured on day 5 after the injection. Results: The ongoing pregnancy rates were higher in the HCG group compared to the control group (86.7% vs. 70.0%, p=0.03). The miscarriage rate was lower in the HCG group (13.3% vs. 30.0%, p=0.03). Those who received HCG also had a higher chance of fetal cardiac pulsation positivity (83.3% vs. 66.7%, p=0.04) and a lower incidence of threatened abortion (10.0% vs. 23.3%, p=0.05). Biochemical analysis revealed higher levels of β-hCG (>1,500 IU/L; 91.7% vs. 71.7%, p=0.01) and progesterone (>10 ng/mL; 83.3% vs. 65.0%, p=0.02). We found weak-to-moderate correlations (r=0.25–0.34, p